UMP is ready to receive 6,334 students back on campus - Mimi Rabita, Abdul Wahit (2021)
PEKAN, 16 September 2021 - Universiti Malaysia Pahang (UMP) is preparing to receive the physical admission of students starting 15 October, involving students who have the need to return to the campus and those who have been fully vaccinated.